(untitled) (Modern education and development, 2025)
the article shows the selection of optimal options for quality service methods when placing and fixing goods on wagons during the delivery process. The means of fastening goods to wagons were researched and measures and proposals for their selection were developed. In addition, the process of fastening the goods was analyzed and proposals were made for fixing the goods to the wagons in order to eliminate the shortcomings of the existing system.